Bone Mass in Children and Adolescents Infected with Human Immunodeficiency Virus - Luiz R.A. de Lima; Rosane C.R. da Silva; Isabela de C.B. Giuliano; Telma Sakuno; Sérgio M. Brincas; Aroldo P. de Carvalho (Elsevier, 2013)
Objective: To describe bone mineral density (BMD) and bone mineral content (BMC) in children and adolescents infected with the human immunodeficiency virus (HIV), and to compare them with data from the National Health and Nutrition Examination Survey IV (NHANES IV). Method: The study included 48 children and adolescents (7 to 17 years old) infected with HIV through vertical transmission. BMC and BMD were measured by dual energy absorptiometry X-ray, by calculating z-scores based on data from NHANES IV. The information on clinical and laboratory parameters of infection by HIV was obtained from medical records. Physical activity, calcium intake, and skeletal maturation were also assessed. Descriptive and inferential statistical procedures were used, with levels of significance set at 5%. Results: Seropositive patients presented lower values compared to data from NHANES IV in all z-scores of bone mass (mean = −0.52 to −1.22, SD = 0.91 and 0.84, respectively). Based on the subtotal z-BMD, there was a prevalence of 16.7% of children and adolescents with low bone mass for age. Individuals using protease inhibitors presented a lower total z-BMD when compared to the group that did not use (−1.31 vs. −0.79, p = 0.02). There were no bone mass differences in relation to physical activity and calcium intake. Conclusions: In the present sample children and adolescents living with HIV have low bone mass for age, and the use of protease inhibitors appears to be related to such decreases. Resumo: Objetivo: Descrever a densidade mineral óssea (DMO) e conteúdo mineral ósseo (CMO) de crianças e adolescentes que vivem com o vírus da imunodeficiência humana e comparar com os dados do National Health and Nutrition Examination Survey IV (NHANES IV). Método: Participaram do estudo 48 crianças e adolescentes (sete a 17 anos de idade) com infecção pelo vírus da imunodeficiência humana adquirida por transmissão vertical. A DMO e o CMO foram mensurados pela absorciometria por dupla emissão de raios-X, calculando-se escores-z com base nos dados do NHANES IV. Nos prontuários médicos foram obtidas as informações dos parâmetros clínicos e laboratoriais da infecção pelo vírus da imunodeficiência humana. Foram ainda avaliadas a atividade física, a ingestão de cálcio e a maturação esquelética. Utilizaram-se procedimentos da estatística descritiva e inferencial, estabelecendo níveis de significância de 5%. Resultados: Os pacientes soropositivos demonstraram valores inferiores comparados aos dados do NHANES IV em todos os escores-z da massa óssea (média = −0,52 a −1,22, dp = 0,91 e 0,84, respectivamente). Com base no z-DMOsubtotal, há uma prevalência de 16,7% de crianças e adolescentes com massa óssea reduzida para a idade. Indivíduos que utilizaram inibidores de protease apresentaram um z-DMOtotal inferior, comparado ao grupo que não utilizou (−1,31 vs. −0,79; p = 0,02). Não foram encontradas diferenças na massa óssea em relação ao nível de atividade física e ingestão de cálcio. Conclusões: Na presente amostra, crianças e adolescentes que vivem com o vírus da imunodeficiência humana possuem baixa massa óssea para idade, e o uso de inibidores de protease parece estar relacionado a tais reduções. Keywords: Bone density, Child, Adolescent, Human immunodeficiency virus, Acquired immunodeficiency syndrome, Life style, Palavras-chave: Densidade óssea, Criança, Adolescente, Vírus da imunodeficiência humana, Síndrome da imunodeficiência adquirida, Estilo de vida